The Artistic Elements In the Works Of Saul Bass (Journal of the College of Basic Education, 2026)
The artistic experience of international designer Saul Bass is one of the most prominent in the field of graphic design. He is considered a creative and exceptional designer who has inspired many in this field, possessing a set of artistic skills that enabled him to address the structure of design discourse in a way that is familiar to the public and connects with them. This research sheds light on that artistic experience and its various elements, which were the main reason behind his success and influence in the field of graphic design and filmmaking. The research problem was manifested in the following question: What are the artistic elements in the works of Shaul Bass? The researcher divided this study into four chapters, as follows: The first chapter was devoted to the research methodology, while the theoretical framework, which constituted the second chapter, covered the literature related to the research topic according to three axes. The first axis represented the intellectual elements that influenced and affected the designer's artistic experience, while the second axis dealt with the technical elements and mechanisms that (Bass) used to construct his design discourse, while the third section dealt with the stylistic data of the designer and how it worked in translating the deep meanings of the topics presented. The researcher devoted the third chapter to the research procedures, choosing a descriptive approach to study the case in order to achieve the research objective. The study, included in the fourth chapter, reached a number of results and conclusions.